Quality Assessment of Some Bottled Water That Available in Erbil City, Iraq by Using Water Quality Index for Drinking Purposes - Toma, Janan Jabbar (Science Journal of University of Zakho, 2013)
Consumers are reacting with water quality problems by buying bottled water which is an expensive solution and only partially resolve the problem. Subsequently, sales of bottled water have increased dramatically in the last ten years; therefore this study was conducted in Erbil city with the major objective of assessing suitability of bottled water quality for drinking purposes through water quality index (WQI) investigation. This was done by subjecting 84 bottled samples collected from different market within 6 months from January to June 2012 to comprehensive physico-chemical analysis using standard methods of analysis. For calculating the WQI, 10 parameters have been considered: Turbidity, Electrical conductivity, Total Dissolved Solids, pH, Alkalinity, Hardness, Calcium, Magnesium, Nitrate and Sulfate. The WQI for these samples ranges from 11.953 to 137.532. Using the water quality index all the bottled samples were classified as excellent to good water they are suitable for drinking purposes except Vauban bottled water which was bad and unsuitable for drinking. A comparison between water quality and the maximum permissible levels depended on the world health organization (WHO) guidelines was reported and discussed. They were varied in composition among the brands and from.